KEKUASAAN SEBAGAI KEKUATAN “OMNIPRESENT” : Penyelidikan Filosofis tentang Konsep Kekuasaan Menurut Michel Foucault - Fatlolon, Costantinus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2014)
In these modern times we can see a dominance of ―juridical-discursive‖ power. This ―juridical-discursive‖ power is exclusively based on law and prohibition, censure, obedience and uniformity of those in power. Foucault recommends a new vision by arguing that power is a multiplicity of connections of force, a process in human relations, and also an aid which at the same time is a strategy which is carried out in certain communities. This power yields everything time and again, it has its source from everywhere and has connections with everything. This power is an omnipresent force. Foucault places power at inter-human relationship. Nevertheless, there is a weakness in Foucault‘s vision, since he puts forward an identification of power-law-monarchy. With this identification, he disregards factual progress of the democratic community.